Removal of Heavy Metal Chromium in Groundwater by Sulfidated and Carboxymethyl Cellulose Modified Nanoscale Zero-valent Iron - Linminhuizhi MA; Jiwei JIA; Qiying FAN; Beiyi XU (Medžiagotyra, 2025)
In this study, nanoscale zero-valent iron (nZVI) was investigated for its effectiveness in removing chromium, a major groundwater contaminant. To enhance nZVI’s removal performance, sulfurization and sodium carboxymethyl cellulose (CMC) modifications were applied. Three preparation methods were used to create modified nZVI materials with distinct structures, and their removal efficiencies were compared. Results showed that the nZVI modified via surface corrosion achieved the highest removal efficiency. Furthermore, the study explored the effects of various factors on the removal efficiency, including the molar ratio of sulfurizing agent to iron, initial pH, reaction temperature, the dosage of modified nZVI, and the initial concentration of hexavalent chromium. The results showed that the highest chromium removal rate (96.97 %) was achieved when the molar ratio of sulfurizing agent to iron was 0.4, the initial pH was 3, the reaction temperature was 25 ℃, the dosage of modified nZVI was 52 mg/L, and the initial hexavalent chromium concentration was 12 mg/L. After three cycles of reuse, the modified nZVI material still maintained a removal rate of 94.73 %. Additionally, the presence of various ions in wastewater was found to influence the removal efficiency. The effect of anions was minimal and could be neglected, while the presence of cations, particularly Mg2+, had a significant impact on removal performance. Under conditions simulating multi-ion groundwater, the modified nZVI material demonstrated a removal rate of up to 90.25 % for hexavalent chromium, highlighting its potential for practical applications.